An Integrative Conceptual Framework of Food Certifications: Systematic Review, Research Agenda, and Macromarketing Implications. (March 2022) - Latino, Maria Elena; Corallo, Angelo; Menegoli, Marta; Nuzzo, Biagio
Food certifications guarantee food quality and reduce information asymmetry regarding food between consumers and producers. There are numerous certifications that facilitate global food systems. While scholars have addressed this issue from several viewpoints, a systematic synchronization of the research in international food certification studies is lacking. The purpose of this study is to explore the field of food certifications. This includes identifying certification definitions, related categories, the main purposes and topics of existing studies in this field. This study uses a systematic literature review. It proposes an integrative conceptual framework, that summarizes the main findings of the study. Additionally, new research routes, as well as both theoretical and macromarketing implications are discussed. This study provides a comprehensive understanding of the international field of food certification, giving researchers, consumers, and food companies a guide to understand the complexity of the global food certification and the related macromarketing effects.